Jatropha curcas as a potential plant for bauxite phytoremediation - Rahim, F. A.A.; Tengku Abdul Hamid, Tengku Haziyamin; Zainuddin, Zarina (Institute of Physics Publishing, 2019)
Abandon bauxite mining sites can cause serious environmental problems, such as poor soil quality, air pollution, erosion and flood. Jatropha curcas could possibly be used to remediate barren bauxite mining sites. The objective of this study was to study the growth performance of J. curcas on top soil (control) and bauxite mined soil. Observation of the plant growth was recorded weekly, including days to rooting, number of roots per cutting, days to new bud opening, number of shoots per cutting, number of leaves per cutting, plant height and chlorophyll content. Data collected on the growth performance of J. curcas were analyzed using SPSS 11.5 for Windows Standard Version. Based on the results obtained, J. curcas could thrive and grow on bauxite mined soil as it has higher significantly difference in number of leaves and plant height after growing on bauxite mined soil. Therefore, J. curcas is suitable for phytoremediation, in order to solve the environmental problems that occur on the bauxite mined site